A condensed heterocyclic compound and its application and an organic electroluminescent device containing the compound
By using new fused heterocyclic compounds as electron transport or hole blocking materials in OLED devices, adjusting electron mobility and injection capabilities, the problems of high driving voltage and low efficiency of existing OLED devices are solved, and longer life is achieved and lower voltage OLED devices.
Patent Information
- Application Number
- CN202211421253.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-14
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-11-14
AI Technical Summary
Existing OLED electronic transmission materials are prone to crystallization, resulting in short device life, high driving voltage and low efficiency.
Develop a new fused heterocyclic compound for OLED devices as electron transport materials or hole barrier materials, adjusting electron mobility and injection capabilities through specific structures, reducing driving voltages and improving device life.
While maintaining OLED efficiency, the working voltage is reduced, the device life is improved, and the problems of high driving voltage and low efficiency are solved.
Smart Images

Figure CN115745962B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic electroluminescence, and in particular to a novel organic compound and application thereof, and an organic electroluminescence device containing the compound. Background Art
[0002] Organic light emitting devices (OLED) are current-driven thin-film devices with a sandwich-like structure, with a single or multiple layers of organic functional materials sandwiched between the anode and cathode. OLED has the characteristics of self-luminescence, wide viewing angle, wide color gamut, short response time, high luminous efficiency, low operating voltage, low cost, and simple production process. It has been widely used in display products such as TVs, smart phones, tablets, car displays, and lighting, and will be further used in creative display products such as large-size displays and flexible screens.
[0003] Organic optoelectronic materials used in OLED devices can be divided into light-emitting layer materials and auxiliary functional layer materials based on their uses. Among them, the light-emitting layer materials include guest materials (also known as light-emitting materials, doping materials) and host materials (also known as matrix materials). Light-emitting materials are divided into fluorescent materials, phosphorescent materials and thermally activated delayed fluorescent materials according to different energy transfer methods. Auxiliary functional layer materials are divided into electron injection materials, electron transport materials, hole blocking materials, electron blocking materials, hole transport materials and hole injection materials according to the different properties of electron or hole transmission speeds.
[0004] Electron transport materials usually have suitable HOMO / LUMO values, which can reduce the driving voltage due to a smaller electron injection barrier. At the same time, they also need to have a higher electron transfer rate, a higher glass transition temperature, and thermal stability. Commonly used electron injection materials in the industry include azole derivatives, quinoline derivatives, and metal chelates, but some materials are easy to crystallize, which can easily lead to a shorter device life. Some materials cannot be effectively matched with the HOMO / LUMO of the adjacent functional layer materials due to their large energy gap, making it impossible to fully utilize energy and the injection barrier is too high, resulting in the device having problems such as excessively high driving voltage and low efficiency.
[0005] Therefore, there is an urgent need in the art to develop a class of OLED electron transport materials that can produce organic electroluminescent devices with high efficiency and long life at low driving voltage. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a novel organic compound, specifically, provides:
[0007] 1) A fused heterocyclic compound for an organic electroluminescent device, wherein the compound is represented by formula (1):
[0008] ACB
[0009] Formula (1)
[0010] Wherein the A unit is a structure shown in formula (A):
[0011]
[0012] The B unit is a structure shown in formula (B):
[0013]
[0014] Where -* indicates the connection position between units;
[0015] The C unit is a naphthylene group;
[0016] wherein L in formula (A) can be selected from a single bond, a substituted or unsubstituted arylene group having 6 to 50 ring carbon atoms, and a substituted or unsubstituted heteroarylene group having 5 to 50 ring atoms; Y1 to Y3 are the same or different from each other and are each independently a N atom or CH, and at least one of Y1 to Y3 is a N atom; Ar1 and Ar2 are the same or different from each other and are each independently a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted heterocyclic group having 5 to 50 ring atoms;
[0017] wherein Y4 to Y6 in formula (B) are the same as or different from each other and are independently a N atom or CR1, and at least one of Y4 to Y6 is a N atom, and R1 is independently selected from a hydrogen atom, a deuterium atom, a halogen atom, a cyano group, a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, a substituted or unsubstituted fluoroalkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 50 ring carbon atoms, a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.
[0018] 2) The fused heterocyclic compound for an organic electroluminescent device according to 1), wherein L is selected from the group consisting of a single bond, a substituted or unsubstituted thienyl, a substituted or unsubstituted furanyl, a substituted or unsubstituted phenyl, a substituted or unsubstituted pyridyl, a substituted or unsubstituted biphenyl, a substituted or unsubstituted naphthyl, a substituted or unsubstituted anthracenyl, a substituted or unsubstituted phenanthryl, a substituted or unsubstituted indenyl, a substituted or unsubstituted fluorenyl, a substituted or unsubstituted spirobifluorenyl, a substituted or unsubstituted indenofluorenyl, a substituted or unsubstituted fluorantheneyl, a substituted or unsubstituted pyrenyl, a substituted or unsubstituted benzothienyl, a substituted or unsubstituted benzofuranyl, a substituted or unsubstituted dibenzothienyl, a substituted or unsubstituted dibenzofuranyl, and a substituted or unsubstituted carbazolyl.
[0019] 3) The fused heterocyclic compound for an organic electroluminescent device according to 1), wherein Ar1 and Ar2 are independently selected from the group consisting of substituted or unsubstituted thienyl, substituted or unsubstituted furanyl, substituted or unsubstituted phenyl, substituted or unsubstituted pyridyl, substituted or unsubstituted biphenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted anthracenyl, substituted or unsubstituted phenanthryl, substituted or unsubstituted indenyl, substituted or unsubstituted fluorenyl, substituted or unsubstituted spirobifluorenyl, substituted or unsubstituted indenofluorenyl, substituted or unsubstituted fluoranthene, substituted or unsubstituted pyrenyl, substituted or unsubstituted benzothienyl, substituted or unsubstituted benzofuranyl, substituted or unsubstituted dibenzothienyl, substituted or unsubstituted dibenzofuranyl, and substituted or unsubstituted carbazolyl.
[0020] 4) The fused heterocyclic compound for an organic electroluminescent device according to 1), wherein the compound is represented by formula (2):
[0021]
[0022] wherein Ar1, Ar2, L, C unit, Y4 to Y6 are as defined in 1).
[0023] 5) The fused heterocyclic compound for an organic electroluminescent device according to 1), wherein the fused heterocyclic compound is selected from the following structures:
[0024]
[0025]
[0026]
[0027]
[0028] 6) An organic electroluminescent device, wherein the organic electroluminescent device comprises an anode, a cathode and at least one organic thin film located between the anode and the cathode, and the organic thin film contains the compound described in any one of 1) to 5).
[0029] 7) The organic electroluminescent device according to 6), characterized in that the compound is used as an electron transport material or a hole blocking material in the organic electroluminescent device.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] By adjusting the electron mobility and enhancing the electron injection capability, the operating voltage can be reduced and the device life can be increased while maintaining the device efficiency, thereby solving the problem of high device driving voltage and low efficiency in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0033] Figure 1 This is a schematic diagram of the structure of an organic electroluminescent device to which the compound of the present invention is applied, wherein the meanings of the various layers of the device structure are as follows:
[0034] 1. Transparent substrate layer, 2. ITO anode layer, 3. Hole injection layer, 4. Hole transport layer A, 5. Hole transport layer B (or electron blocking layer), 6. Light-emitting layer, 7. Electron transport layer B (or hole blocking layer), 8. Electron transport layer A, 9. Electron injection layer, 10. Cathode reflective electrode layer. DETAILED DESCRIPTION
[0035] The principles and features of the present invention are further illustrated below by taking a number of synthetic examples as examples. The examples given are only used to explain the present invention but are not used to limit the scope of the present invention.
[0036] The following are the methods for synthesizing specific compounds of formula (1).
[0037] Synthesis Example 1: Synthesis of Chemical 2
[0038]
[0039] Synthesis of intermediate 1a:
[0040] Weigh 4.16g (20mmol, 1.0eq) 2-bromoquinoline, 4.55g (22mmol, 1.1eq) 4-chloro-1-naphthaleneboronic acid, 0.46g (0.4mmol, 0.02eq) tetrakistriphenylphosphine palladium, 5.5g (40mmol, 2.0eq) potassium carbonate into a flask, evacuate, protect with nitrogen, add 50ml of deoxygenated dioxane and 10ml of water, reflux at 80℃ for 12h. Stop the reaction, cool to room temperature, extract with ethyl acetate, wash with water three times, concentrate the solvent, separate with silica gel column, and obtain 5.33g of white solid 1a, with a yield of 92%. The molecular weight measured by mass spectrometry is m / z=289.9 (M+H)+
[0041] Synthesis of Chemical 2:
[0042] Weigh 2.90g (10mmol, 1.0eq) of intermediate 1a, 4.79g (11mmol, 1.1eq) of 1b, 0.18g (0.20mmol, 0.02eq) of tris(dibenzylideneacetone)dipalladium, 0.36g (0.80mmol, 0.08eq) of 2-dicyclohexylphosphine-2,4,6-triisopropylbiphenyl, and 2.75g (20mmol, 2.0eq) of potassium carbonate into a flask, evacuate the air, protect with nitrogen, add 50ml of deoxygenated dioxane and 10ml of water, and reflux at 100°C for 12h. Stop the reaction, cool to room temperature, extract with ethyl acetate, wash with water three times, concentrate the solvent, and recrystallize with ethyl acetate to obtain 4.61g of white solid 2, with a yield of 81%. The molecular weight measured by mass spectrometry is m / z=563.1 (M+H)+
[0043] Synthesis Example 2: Synthesis of Chemical 11
[0044]
[0045] Synthesis of intermediate 2a:
[0046] Weigh 4.16g (20mmol, 1.0eq) 3-bromoquinoline, 4.55g (22mmol, 1.1eq) 4-chloro-1-naphthaleneboronic acid, 0.46g (0.4mmol, 0.02eq) tetrakistriphenylphosphine palladium, 5.5g (40mmol, 2.0eq) potassium carbonate into a flask, evacuate, protect with nitrogen, add 50ml of deoxygenated dioxane and 10ml of water, reflux at 80℃ for 12h. Stop the reaction, cool to room temperature, extract with ethyl acetate, wash with water three times, concentrate the solvent, separate with silica gel column, and obtain 5.28g of white solid 2a, with a yield of 90%. The molecular weight measured by mass spectrometry is m / z=289.9 (M+H)+
[0047] Synthesis of Chemical 11:
[0048] 2.90 g (10 mmol, 1.0 eq) of intermediate 2a, 4.78 g (11 mmol, 1.1 eq) of 2,4-diphenyl-6-[4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl]-1,3,5-triazine, 0.18 g (0.20 mmol, 0.02 eq) of tris(dibenzylideneacetone)dipalladium, 0.36 g (0.80 mmol, 0.08 eq) of 2-dicyclohexylphospho-2,4,6-triisopropylbiphenyl, and 2.75 g (20 mmol, 2.0 eq) of potassium carbonate were weighed into a flask, the mixture was evacuated and purged with nitrogen, 50 ml of deoxygenated dioxane and 10 ml of water were added, and the mixture was refluxed at 100°C for 12 h. The reaction was stopped, cooled to room temperature, extracted with ethyl acetate, washed three times with water, the solvent was concentrated, and recrystallized with ethyl acetate to obtain 4.90 g of white solid 11 with a yield of 87%. The molecular weight measured by mass spectrometry was m / z=563.3 (M+H)+
[0049] Synthesis Example 3: Synthesis of Chemical 13
[0050]
[0051] 2.90 g (10 mmol, 1.0 eq) of intermediate 1a, 4.78 g (11 mmol, 1.1 eq) of 2,4-diphenyl-6-[4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl]-1,3,5-triazine, 0.18 g (0.20 mmol, 0.02 eq) of tris(dibenzylideneacetone)dipalladium, 0.36 g (0.80 mmol, 0.08 eq) of 2-dicyclohexylphospho-2,4,6-triisopropylbiphenyl, and 2.75 g (20 mmol, 2.0 eq) of potassium carbonate were weighed and added into a flask. The flask was vented and protected with nitrogen. 50 ml of deoxygenated dioxane and 10 ml of water were added, and the mixture was refluxed at 100 °C for 12 h. The reaction was stopped, cooled to room temperature, extracted with ethyl acetate, washed three times with water, the solvent was concentrated, and recrystallized with ethyl acetate to obtain 4.73 g of white solid 13 with a yield of 84%. The molecular weight measured by mass spectrometry was m / z=563.3 (M+H)+
[0052] Synthesis Example 4: Synthesis of Chemical 24
[0053]
[0054] Synthesis of intermediate 4a:
[0055] Weigh 6.86g (20mmol, 1.0eq) 2-([1,1'-biphenyl]-3-yl)-4-chloro-6-phenyl-1,3,5-triazine, 4.4g (22mmol, 1.1eq) 4-bromophenylboronic acid, 0.46g (0.4mmol, 0.02eq) tetrakistriphenylphosphine palladium, 5.5g (40mmol, 2.0eq) potassium carbonate into a flask, evacuate, protect with nitrogen, add 100ml of deoxygenated tetrahydrofuran and 20ml of water, reflux at 80℃ for 12h. Stop the reaction, cool to room temperature, extract with ethyl acetate, wash with water three times, concentrate the solvent, separate with silica gel column, and obtain 7.78g of white solid 4a, with a yield of 84%. The molecular weight measured by mass spectrometry is m / z=464.1 (M+H)+
[0056] Synthesis of intermediate 4b:
[0057] Weigh 4.64g (10mmol, 1.0eq) of intermediate 4a, 3.05g (12mmol, 1.2eq) of biboric acid pinacol ester, 0.22g (0.30mmol, 0.03eq) of [1,1'-bis(diphenylphosphino)ferrocene] dichloropalladium, and 0.2g (20mmol, 2.0eq) of potassium acetate into a flask, evacuate, protect with nitrogen, add 50ml of deoxygenated dioxane, and reflux at 100°C for 12h. Stop the reaction, cool to room temperature, extract with ethyl acetate, wash with water three times, concentrate the solvent, and recrystallize with ethyl acetate to obtain 3.98g of white solid, with a yield of 78%. The molecular weight measured by mass spectrometry is m / z=511.8 (M+H)+ Synthesis of Chemical 24
[0058] 2.90g (10mmol, 1.0eq) of intermediate 2a, 5.6g (11mmol, 1.1eq) of intermediate 4b, 0.18g (0.20mmol, 0.02eq) of tris(dibenzylideneacetone)dipalladium, 0.36g (0.80mmol, 0.08eq) of 2-dicyclohexylphosphine-2,4,6-triisopropylbiphenyl, and 2.75g (20mmol, 2.0eq) of potassium carbonate were added to the flask, evacuated, nitrogen protected, 150ml of deoxygenated dioxane and 30ml of water were added, and the reaction was refluxed at 100°C for 12h. The reaction was stopped, cooled to room temperature, extracted with ethyl acetate, washed with water three times, the solvent was concentrated, and recrystallized from ethyl acetate to obtain 5.81g of white solid 24, with a yield of 91%. The molecular weight measured by mass spectrometry was m / z=639.3 (M+H)+
[0059] Synthesis Example 5: Synthesis of Chemical 56
[0060]
[0061] Synthesis of intermediate 5a:
[0062] 3.56g (10mmol, 1.0eq) 2-(9H-carbazole)-4-chloro-6-phenyl-1,3,5-triazine, 2.2g (11mmol, 1.1eq) 4-bromophenylboronic acid, 0.23g (0.2mmol, 0.02eq) tetrakistriphenylphosphine palladium, 2.75g (20mmol, 2.0eq) potassium carbonate were weighed and added into the flask, purged and purged, nitrogen was protected, 60ml of deoxygenated tetrahydrofuran and 15ml of water were added, and the reaction was refluxed at 70°C for 12h. The reaction was stopped, cooled to room temperature, extracted with ethyl acetate, washed with water three times, the solvent was concentrated, and separated by silica gel column to obtain 4.29g of white solid 4a, with a yield of 90%. The molecular weight measured by mass spectrometry was m / z = 476.8 (M+H) +
[0063] Synthesis of intermediate 4b:
[0064] Weigh 4.77g (10mmol, 1.0eq) of intermediate 4a, 3.05g (12mmol, 1.2eq) of biboric acid pinacol ester, 0.22g (0.30mmol, 0.03eq) of [1,1'-bis(diphenylphosphino)ferrocene] dichloropalladium, and 0.2g (20mmol, 2.0eq) of potassium acetate into a flask, evacuate, protect with nitrogen, add 80ml of deoxygenated dioxane, and reflux at 100°C for 12h. Stop the reaction, cool to room temperature, extract with ethyl acetate, wash with water three times, concentrate the solvent, and recrystallize with ethyl acetate to obtain 4.15g of white solid, with a yield of 79%. The molecular weight measured by mass spectrometry is m / z=524.8 (M+H)+ Synthesis of Chemical 56
[0065] 2.90g (10mmol, 1.0eq) of intermediate 1a, 5.78g (11mmol, 1.1eq) of intermediate 4b, 0.18g (0.20mmol, 0.02eq) of tris(dibenzylideneacetone)dipalladium, 0.36g (0.80mmol, 0.08eq) of 2-dicyclohexylphosphine-2,4,6-triisopropylbiphenyl, and 2.75g (20mmol, 2.0eq) of potassium carbonate were weighed and added into the flask, purged and purged, nitrogen was protected, 150ml of deoxygenated dioxane and 30ml of water were added, and the mixture was refluxed at 100°C for 12h. The reaction was stopped, cooled to room temperature, extracted with ethyl acetate, washed with water three times, the solvent was concentrated, and recrystallized from ethyl acetate to obtain 5.61g of white solid 56, with a yield of 86%. The molecular weight measured by mass spectrometry was m / z=652.3 (M+H)+
[0066] Device Example: Fabrication of Organic Electroluminescent Devices Using Electron Transport Materials
[0067] A 25 mm × 75 mm × 1.1 mm thick glass substrate with an indium tin oxide (ITO) transparent electrode (anode) was ultrasonically cleaned in isopropyl alcohol for 5 minutes and then cleaned with ultraviolet (UV)-ozone for 30 minutes. The ITO film thickness was 130 nm. The cleaned glass substrate was mounted on the substrate rack of a vacuum evaporation device and evacuated to 1×10 -5 ~1×10 -6 Pa, evaporate the hole injection layer (HIL) HATCN on the ITO transparent conductive layer with a thickness of 15nm. Evaporate the hole transport layer A (HTL) on the hole injection layer with a thickness of 60nm. Then, evaporate the electron blocking layer (EBL) on the hole transport layer A with a thickness of 5nm. Then, co-evaporate the luminescent layer (EML) on the electron blocking layer with a thickness of 20nm. The luminescent layer (EML) is evaporated by multi-source co-evaporation to deposit the luminescent material BD and the main material BH of the luminescent layer, wherein the doping concentration of the luminescent material is 2 wt%. In order to ensure the accuracy of the doping concentration of the luminescent material, it is necessary to wait for the evaporation rate of the luminescent material and the main material to stabilize, and then open the shielding baffle to perform multi-source co-evaporation. Then evaporate the hole blocking layer (HBL) 7 with a thickness of 5nm on the luminescent layer. Then evaporate the electron transport material (ETL) and 8-hydroxyquinoline lithium (Liq) on the hole blocking layer with a thickness of 30nm and a doping ratio of 1:1. In addition, an electron injection electrode (EIL) is evaporated on the ETL to a thickness of 1 nm. Then, a metal cathode aluminum (Al) is evaporated on the EIL to a thickness of 100 nm. The structure of the organic electroluminescent device of Example 1 is as follows: Figure 1 As shown, Figure 1 The stacking order and role of each functional layer are also shown.
[0068] The OLED has the following layer structure in principle: substrate / hole injection layer (HIL) / hole injection layer (HTL) / electron blocking layer (EBL) / luminescent layer (EML) / hole blocking layer (HBL) / electron transport layer (ETL) / electron injection layer (EIL) and finally cathode. The cathode is formed by an aluminum layer with a thickness of 100 nm. The molecular structure of the materials used for OLED is partially shown in Table 1.
[0069] Table 1 Materials used for OLED
[0070]
[0071]
[0072] Device Examples 1-5: Fabrication of Organic Electroluminescent Devices Used as Electron Transport Materials
[0073] Table 2 Compounds of the present invention used in the electron transport layer of device examples
[0074]
[0075] The device structure of device embodiment 1 is specifically: ITO (130) / HATCN (15) / HTL (60) / EBL (5) / BH: BD (20, 2% by weight) / HBL (5) / Chemical 2: Liq (30, 50% by weight) / Liq (1) / Al (100). It should be noted that the numbers in parentheses represent the film thickness (unit: nm).
[0076] The only difference between device examples 2 to 5 and device example 1 is that the compound 2 of the present invention used in the electron transport layer is replaced by other compounds of the present invention, as shown in Table 4 for details.
[0077] Comparative Examples 1 to 3:
[0078] Table 3. Compounds used in the electron transport layer of the comparative example
[0079]
[0080] Compared with Example 1, Comparative Examples 1 to 3 differ in that the electron transport layer material in the organic electroluminescent device is changed to REF-1 to REF-3 with similar structures reported in the industry. The obtained device performance test data are shown in Table 4.
[0081] The OLEDs were characterized by standard methods. For this purpose, the electroluminescence spectrum, the current efficiency (measured in cd / A) were determined, which was calculated as a function of the luminous density from the current / voltage / luminous density characteristic (IUL characteristic) exhibiting Lambertian emission characteristics. 2 The required voltage V1000 is determined at the brightness of 1000cd / m 2 Finally, EQE1000 means the current efficiency achieved at a brightness of 1000cd / m 2 External quantum efficiency at working brightness, T95 means the device is 1000cd / m 2 The operating time from the initial brightness of the device to 95% of the brightness.
[0082] Table 4
[0083]
[0084] As can be seen from Table 4, compared with the prior art, the device embodiments 1 to 5 of the present invention can reduce the driving voltage and increase the life of the device while maintaining the current efficiency of the OLED. For example, the driving voltage V1000 of the device embodiment 2 where chemical 11 is located is reduced from 4.1V to 3.7V compared to comparative example 2, and more importantly, the device life T95 is increased by 56.7%. This is mainly because the protective material of the present invention connects the A and B units at specific positions through the naphthalene unit, which can effectively adjust the mobility of the material and reduce the electron injection barrier, thereby reducing the driving voltage and increasing the device life.
Claims
1. A fused heterocyclic compound for an organic electroluminescent device, characterized in that: The fused heterocyclic compound is selected from the following structures:
2. An organic electroluminescent device, characterized in that: The organic electroluminescent device comprises an anode, a cathode and at least one organic thin film between the anode and the cathode, wherein the organic thin film contains the fused heterocyclic compound according to claim 1.
3. The organic electroluminescent device according to claim 2, characterized in that: The fused heterocyclic compound is used as an electron transport material or a hole blocking material in an organic electroluminescent device.